A bout of treadmill exercise increases matrix metalloproteinase-9 activity in the rat hippocampus. (6th May 2015) - Nishijima, Takeshi; Kawakami, Masashi; Kita, Ichiro
Highlights: We examined changes in MMP-9 activity in the rat hippocampus following exercise. MMP-9 activity in the rat hippocampus was increased 12 h after mild exercise. MMP-9 might be a new molecular target regulating exercise-induced hippocampal plasticity. Abstract: Regular exercise induces a variety of structural changes in the hippocampus of rodents, although the underlying mechanisms remain obscure. Particularly, the possible involvement of molecules regulating the remodeling of the extracellular matrix (ECM) is under-studied. Matrix metalloproteinase-9 (MMP-9), an extracellular protease, plays a critical role in regulating neuronal plasticity by remodeling the ECM in the brain. The current study used gel zymography to examine for changes in the proteolytic activity of MMP-9 in the rat hippocampus following a bout of treadmill exercise at mild (10 m/min) or moderate (25 m/min) intensity. We found that MMP-9 activity was significantly increased at 12 h after mild treadmill exercise. However, the activity of MMP-2 and the expression level of the tissue inhibitor of metalloproteinase-1 (TIMP-1) were unchanged following exercise. These findings suggest that exercise triggers MMP-9 activation in the hippocampus, which might be a new molecular mechanism of exercise-induced hippocampal plasticity.